Wings of Judgment : American Bombing in World War II. (Oxford University Press, USA, 1988)
A disturbing and perceptive study of the strategy, outcome, and choices behind the American bombing policies of World War II. The author analyses the explanations and moral arguments used by America's military leaders to justify the attacks on Dresden, Berlin, and Hiroshima.